Analysis hybrid working, performance effectivity, and employee’s collaboration - Mildawani, Maria Margaretha Tri Susetyaning; Wonte, Gracia Ayu Chety (Edelweiss Applied Science and Technology, 2024)
This study examines the influence of hybrid working on performance effectiveness and employee collaboration at PT. XYZ. We employed probability sampling via cluster randomized sampling to select respondents from seven business units. Primary data collection involved observation, interviews, and Google Form questionnaires. We adopted a quantitative approach utilizing correlation analysis and hypothesis testing. The study uncovered a robust correlation between hybrid working and performance effectiveness, contributing significantly to both performance and collaboration. Male employees demonstrated higher performance effectiveness than females, despite a moderate correlation. However, female employees still exhibited notable performance effectiveness, attributed to work-life balance. Departments that were adaptable to technology and less reliant on hardcopy methods showed heightened performance effectiveness. The findings underscore the importance of embracing hybrid working arrangements for improved performance effectiveness and enhanced collaboration. We encourage organizations to implement and optimize hybrid work policies to reap these benefits. Prioritizing work-life balance, particularly for female employees, is crucial for fostering satisfaction and productivity. Additionally, investing in technological infrastructure and providing training can enhance performance effectiveness by enabling proficient use of digital tools and platforms.